Therapy with non-steroidal anti-inflammatory drugs and the quality of life of patients with rheumatic diseases - E. Yu. Polishchuk; A. E. Karateev; V. N. Amirdzhanova (Современная ревматология)
The modern strategy for the treatment of rheumatic diseases (RD) involves the fastest possible achievement of remission or low disease activity. However, even with the use of the most modern technologies and after a pronounced decrease in the inflammatory activity of the disease, it is not always possible to achieve a complete and stable remission. In such a situation, an important goal of treatment is to maximize the quality of life (QoL) of patients. Pain is one of the leading predictors of a decrease in QoL in patients with RD. At the same time, effective pain control can improve not only the course of individual symptoms of the disease, but also life prognosis as a whole. Non-steroidal anti-inflammatory drugs (NSAIDs) are the most popular drugs for the symptomatic treatment of RD. At the same time, the administration of NSAIDs with a favorable safety profile can improve the quality of life of patients. Meloxicam is the first predominantly selective inhibitor of cyclooxygenase (COX) 2, which appeared in the arsenal of practitioners in the late 90s and has a strong evidence base for efficacy and safety.